Model and algorithm of creation of silicon photodiod with high sensitivity in the middle infrared area of the spectrum - Dobrovolsky, Yuri; Sorokatyi, Yurii (Radìoelektronnì ì komp'ûternì sistemi (Online), 2022)
The sensitivity of the photodiode will depend on the amount of radiation power that it must register. The characteristics of a photodiode, as is known, are determined by its design. In particular, the characteristics of the material used, the configuration of electric fields, the mobility of charge carriers, the width of the SCR (space charge region), etc. Additionally, the characteristics of the photodiode are determined by the external applied voltage and the wavelength of the received optical radiation. In the case of its absorption only in the SCR (region of space charge) and at small distances around it, for example, in a p-i-n photodiode, its frequency characteristics will be determined mainly by the flight time of the generated charge carriers through the SCR. .The subject is to create an algorithm for building a photodiode, which must work at a certain wavelength, for example, at a wavelength of 0.95 μm. Silicon of the p-type conductivity with a specific resistance of at least 10 kΩ • cm was chosen as the starting material. The goal is to create a model and algorithm for developing a photodiode capable of providing maximum values of current monochromatic sensitivity due to the maximum collection of photogenerated charge carriers in its volume at the appropriate external bias. Task: To fulfill this requirement, theoretical and experimental research must be conducted. Methods: technological processes for manufacturing the proposed photodiode can be similar to the processes of forming planar p-i-n photodiodes based on silicon. The proposed technical solution determines the correlation between the area of collection of photogenerated charge carriers and the area of their generation. The result can be achieved by changing the design of the photodiode crystal, considering the obtained theoretical conclusions. Results: An analysis of the factors determining the current monochromatic sensitivity of the photodiode was carried out. A design of a photodiode with increased sensitivity compared to a serial photodiode of the FD - 309 type has been developed. Conclusions: The proposed calculation was used to estimate the sensitivity of the photodiode. The operating voltage and, accordingly, the width of the OPZ (area of space charge) W was chosen considering the absorption depth of the operating wavelength of 0.95 μm. The calculation shows that the current monochromatic sensitivity of such a photodiode can be increased to 0.57 A/W in contrast to the declared sensitivity of 0.5 A/W. Comparative studies of the produced batch of created photodiodes and FD - 309 photodiodes were conducted, which showed that the proposed photodiode really has a current monochromatic sensitivity at a wavelength of 0.95 μm not less than 0.55 A/W. Simultaneously, its rise time is reduced from 50 ns to 10 ns, and the capacitance is 90 pF instead of 100 pF in FD - 309.